Determinants of the financial structure of small industrialists in the Junin region - Ramírez-Arellano, Miguel A. (2022)
Objective: To explain the factors that determine the financial structure of small industrialists in the province of Tarma, Junín (Peru). Methods. The approach was quantitative, basic type, explanatory-retrospective level and non-experimental design. The instrument used was developed for the purpose of the research, whose dimensions were: "size", "asset structure", "resource generation capacity" and "years of operation". The sample consisted of 13 industrial SMEs in the province of Tarma. The sampling was non-probabilistic-intentional. Results. The dimensions "size", "level of assets" and "capacity to generate resources", with a coefficient of multiple determination (R2) of 0.852 and a p-value of 0.00001 indicate a strong influence on the financial structure. Conclution. The factors that determine the financial structure of small industrialists in Tarma are: size, level of assets, and capacity to generate resources.